Optimization of Lipid Extraction from Municipal Scum Sludge for Biodiesel Production Using Statistical Approach - Ibrahim, Samir Hag; Hamza, Emad (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
Design of Experiment (DoE) as a statistical method was applied for optimizing lipid extraction conditions from scum sludge. Four different extraction variables were optimized namely methanol to hexane ratio (%), solvent to sludge ratio (ml/g), temperature (oC), and extraction time (h). Process optimization was conducted through three main steps: 1) 2k factorial screening design; 2) Steepest ascent method; and 3) Box-Behnken design and response surface method. Based on 2k factorial screening design, methanol to hexane ratio, solvent to sludge ratio and temperature were identified as highly significant variables affecting lipid extraction from scum sludge. Based on screening results, the steepest ascent method was used followed by Box-Behnken design and Response Surface Method (RSM) were then applied for optimization. The maximum extracted lipid of 29.4% (wt lipid/wt dry sludge- %) was achieved at 40% methanol to hexane ratio (%), 40 solvent to sludge ratio (ml/g), 90oC and 6 hours extraction time. The results revealed that lipid extraction increases with reducing the methanol to hexane ratio, increasing solvent to sludge ratio and increasing temperature The results demonstrated the potentiality of scum sludge for biodiesel production from scum sludge compared with the amount of lipid extracted from primary and secondary sludge reported by other studies.Article History: Received Feb 16th 2017; Received in revised form May 5th 2017; Accepted June 4th 2017; Available onlineHow to Cite This Article: Ibrahim, S.N.H, and Hamza, E.A. (2017). Optimization of Lipid Extraction from Municipal Scum Sludge for Biodiesel Production Using Statistical Approach. International Journal of Renewable Energy Development, 6(2), 171-179.https://doi.org/10.14710/ijred.6.2.171-179